Comparative transcriptome analysis provides insights into molecular pathway and genes associated with head-type formation and phenotypic divergence in Chinese cabbage - Meng, Chuan; Liu, Xiaodong; Wu, Fang; Ma, Lei; Wang, Yuhai; Mu, Jingui; Wang, Mingqiu (Frontiers in Genetics, 2023)
Background: The heading type of Chinese cabbage is a significant commercial trait with high economic value. At present, research on the phenotypic divergence and formation mechanism of heading type is limited. Results: Through comparative-transcriptome analysis, the formation and phenotypic divergence mechanism of the leafy head of diploid overlapping type cabbage, diploid outward-curling type cabbage, tetraploid overlapping type cabbage, and tetraploid outward-curling type cabbage were systematically and comprehensively investigated, and the phenotype-specific genes of four varieties were revealed. These phenotype-specific differentially expressed genes (DEGs) were considered crucial for cabbage heading type through WGCNA. Some transcription factors have been predicted as significant genes for phenotypic divergence, including the members of the bHLH, AP2/ERF-ERF, WRKY, MYB, NAC, and C2CH2 families. Phytohormone-related genes, including abscisic acid/auxin hormone, may play an important role in the phenotypic divergence of head type in cabbage. Conclusion: Comparative-transcriptome analysis supports a role for phytohormone-related genes and some transcription factors in head-type formation and divergence for four cultivars. These findings increase our understanding of the molecular basis for pattern formation and divergence of the leafy heads of Chinese cabbage and will contribute to developing more desirable leafy head patterns.